2018
DOI: 10.3390/buildings8100138
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Leaves Densities as Parameter for Effectiveness of Energy Transfer on the Green Facade

Abstract: This research involves the study of two models of green facades and a model of bare wall. A house miniature was used as thermal lab. The aim of the project is evaluating the performance of energy transfer based on the various leaves densities on the green facade. Heat calculation was used to calculate heat transfer on the wall surface. There are two kinds of leaves densities, 50% and 90%. The data measurement show that the green facade has a significant cooling effect and more visible for the facade with highe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 24 publications
2
13
0
1
Order By: Relevance
“…Widiastuti et al [15] also found that the lowest difference up to 0.30 • C between exterior and interior surfaces temperature occurred on the green façade with higher leaves densities. Using the Newton cooling law calculation, the authors also found that during day time, heat flux on the green façades with higher leaves densities was negative.…”
Section: Introductionmentioning
confidence: 90%
See 4 more Smart Citations
“…Widiastuti et al [15] also found that the lowest difference up to 0.30 • C between exterior and interior surfaces temperature occurred on the green façade with higher leaves densities. Using the Newton cooling law calculation, the authors also found that during day time, heat flux on the green façades with higher leaves densities was negative.…”
Section: Introductionmentioning
confidence: 90%
“…As mentioned in the introduction, to study the effect of the greenery layer on building thermal characteristics, three kinds of green façades were installed with different leaves covered areas in Semarang City, around Architecture Department at Diponegoro University. They included a non planted wall (experiment I), green façade with 50% leaves covered area (experiment II), and green façade with 90% leaves covered area (experiment III) [15]. At that moment, the building model placed behind other buildings and surrounded by large trees can be seen in Figure 1.…”
Section: Object Studymentioning
confidence: 99%
See 3 more Smart Citations